Hubungan antara Sosial Ekonomi, Demografi dan Kualitas Konsumsi Pangan dengan Status Gizi - Putra, Muh. Guntur Sunarjono; Kustiyah, Lilik; Dwiriani, Cesilia Meti (Puslitbang Sinergis Asa Professional, 2024)
National development is successful when quality human resources are available, which requires early preparation during adolescence with good nutritional status. Nutritional issues among adolescents in West Java Province, particularly stunting (24.1%) and overweight (16.9%) among individuals aged 13–15 years, remain high. These issues are influenced by suboptimal socioeconomic and demographic factors, as well as the low quality and diversity of food consumption, especially in animal-based foods (24%) and fruits and vegetables (16.9%). This study aimed to analyze the relationship between socioeconomic factors, demographics, and food consumption quality with nutritional status. A cross-sectional design was employed using primary data from 88 participants. The study was conducted in February 2024 at SMP Negeri 1 Cibungbulang and SMP Negeri 2 Cibungbulang. Participants were selected through purposive sampling based on inclusion and exclusion criteria. Inclusion criteria included grade VII students willing to participate in the study, while exclusion criteria included those unwilling to participate or with incomplete data.Statistical tests employed included descriptive analysis and relationship tests (Spearman and Chi-Square tests). The findings revealed significant relationships between maternal education level (p=0.013) and maternal employment status (p=0.041) with adolescent nutritional status. Additionally, food consumption quality showed a significant relationship with nutritional status (p=0.016). In conclusion, socioeconomic factors, demographics (maternal education level and employment status), and food consumption quality play critical roles in achieving optimal nutritional status among adolescents.